Influence of bent down conductor for lightning protection system - Md. Ariffen, Amizah (2017)
Down conductor is one of the pivotal parts of the Lightning Protection System. It plays a key role in rerouting lightning captured by the air termination system to the earth termination system. In Malaysia, the standard practice for lightning protection is adapted from the International Electrotechnical Commission, which consists of the IEC 62305 series. For the enhancement and safe protection from lightning, external and internal lightning protection is compulsory for each protected structure (building). A straight down conductor, is ideally suited for the best-case scenario regarding reliability and safety protection. One to aesthetical aspects, down conductor is undesirably bent in most current buildings. However, only the primary bare type of a down conductor is undergone such process, and bent at a certain degree which depending on the structure itself. Neither the Malaysian Standard, IEC, nor Institute of Electrical and Electronics Engineers has ever specified the permitted bending degree of the down conductor. Therefore, the purpose of this research is to evaluate the bending degree effect on down conductors, by looking at electric field distribution around the bent area with the presence of concrete wall and reinforcement bar. The numerical analysis performed in this study referenced the implied (not formalised) manufacturing down conductor specifications which use entirely copper materials for the down conductor. The use of aluminum and galvanised iron types are also evaluated in this study. Three conditions of angles of the down conductor; smaller than 90º angles, 90º and wider than 90º angles are modelled with a minimum cross-sectional area according to the standard for the worst-case scenario with the implementation of the lightning protection system. Experimental work is further conducted to validate the results from conducting the numerical analysis. This is to ensure accuracy and completeness of the results. A thorough evaluation of the electric field is analysed in correlation with the critical breakdown value. In this study, it was determined that the bending down conductors had a significant effect on electric field distribution at the bent (vertex) area with the interaction of concrete wall and reinforcement bar. The smaller the angles of the bending down conductor, the more this contributed to intensifying the electric field in the bent area, especially at the inner part of the angle that was less than 90º. For the 90 º angle, the electric field distribution is considered lower compared with the smaller angle and for the wider than 90º angles, it is less than the previous angles conditions. Therefore, that critical bent would be the ones with smaller than 90º, i.e. 30º and 60º. Hence, it could be concluded that, the optimum angle which is more than 90º is proposed for down conductor installation of a protective structure. This is because the lower electric field reduce the chances of arcing occurrences to the nearby human and structure. Thus, this rule should be adapted as an important guideline for the contractors, and architects in the building construction industry. This proved beneficial for designing the lightning protection system to achieve best safety and protection.